Разработка обобщенной процессной модели прецедента, метода его формирования и использования - Чалый, С.Ф.; Левыкин, И.В. (Управляющие системы и машины, 2016)
Разработана общая модель прецедента, задающая с использованием процессного представления особенности его применения в конкретной предметной области. Рассмотрена последовательность применения прецедентного подхода к решению функ циональных задач информационной системы, разработан метод формирования, выбора, корректировки, сохранения текущего и прецедента-аналога. Розроблено узагальнену модель прецеденту, що задає особливості його застосування в конкретній предметній області за до помогою процесного опису. Розглянуто послідовність застосування прецедентного підходу до управління підприємством, ро зроблено метод формування, вибору, коригування, збереження поточного і прецеденту-аналога. The problem of modeling on the Case-Based reasoning in solving the functional tasks of information systems is considered. The Case-based reasoning modeling makes it possible to use knowledge and experience available to solve the current problems even in the case of some differences between the problem been solved and the current problem. In using the knowledge on the issues available, arises the question of the model of case-based reasoning developing that should formalize the problem solution process as well as the method of model-building technique. The content of the case depends on the features of data domain that makes it difficult to build the generalized model. However, the problem solution for any study-case can be shown as the execution sequence, viz. a process. So, the purpose of this research is to generalize the case-study representation using a process approach. The generalized model of the study-case including a set of possible processes for solving the problem, local results of solutions and restrictions in the data domain is proposed. Each process of the problem solving consists of a sequence of events that reflect the chain of actions that must be done to solve the task. Selection of the particular possible processes of the problem solution depends on the sub-product desired, as well as on the data domain restrictions. On the practical level, the proposed model makes it easy to adapt the study-case based on the problem solution selection. Implementation of the process approach based on the proposed model of the case-base reasoning includes a number of successive steps providing method for forming the initial data, their selection and correction as well as saving the current prototype and study-case prototype. The method allows to form the problem solution on the base of using mining technology to develop a process of the problem solution. Besides, it makes possible to implement an adaptive control using the event attributes.